Adsorbed Cr(VI) based activated carbon/polyaniline nanocomposite: A superior electrode material for asymmetric supercapacitor device. (15th July 2020) - Acharya, Sourav; Sahoo, Sumanta; Sonal, Sonalika; Lee, Joong Hee; Mishra, Brijesh K.; Nayak, G.C.
Abstract: Combating heavy metal pollution and energy crisis together, while maintaining the green chemistry standard is a great challenge. Among heavy metals, the toxicity of hexavalent chromium compounds is well known, one which can be adsorbed from water and can be used as an electrode for energy storage. In this work, a nanocomposite of exhausted activated carbon (extracted from commercial water filter) and polyaniline was used as an adsorbent for toxic Cr(VI) adsorption from mine water, and a high-performance asymmetric energy storage device was developed from it. Firstly, the adsorbent was explored for the proficient removal of toxic Cr(VI) from water. The adsorption data was found to be well fitted with the Langmuir isotherm, and the pseudo-second order kinetics suggested the monolayer chemisorbed nature. In the next step, the adsorbed material was investigated as the cathode material for supercapacitors. The nanocomposite based on Cr(VI)-adsorbed material exhibited a high specific capacitance of 219.6 F/g at 1 A/g current density and moderate cycling stability of 77% after 5000 charges/discharge cycles. An asymmetric device developed using this hybrid material achieved an elevated energy density of 60.8 Wh/kg in organic electrolyte. The device was used to light up a strip of 43 red LEDs connected in parallel. Graphical abstract: A cost-effective approach to mitigate two of the major problems of toxicity of mine water and energy storage have been proposed by fabrication of asymmetric supercapacitors through the adsorption of Cr(VI) from mine water with modified filter-derived activated carbon. The incorporation of Cr(VI) and subsequent conversion to Cr(III) enhanced the performance of the electrode towards energy storage. This approach will facilitate both water purification and development of efficient electrodes for energy storage. Image 1 Highlights: Cr (VI) removal from mine water by modified activated carbon-based nanocomposite. Fabrication of asymmetric supercapacitor device by "Waste to Wealth" approach. Waste management and Development of Efficient Energy storage devices.